A Narrative Inquiry into a Female Athlete's Experiences with Protracted Concussion Symptoms. Issue 6 (18th August 2017) - Caron, Jeffrey G.; Schaefer, Lee; André-Morin, Daphnée; Wilkinson, Shawn
ABSTRACT: This article explores a female university volleyball student-athlete's experience with protracted concussion symptoms. Through the methodology of narrative inquiry, four salient themes became apparent related to Daphnée's experiences: (a) "I felt so alone, " (b) "I had to make one of the hardest decisions of my life, " (c) "I feel like I'm in prison, " and (d) "There's no light at the end of the tunnel." Overall, this study offers a rare look into the impact of concussion on an individual's athletic and academic identities, career progression, and in turn, her imagined stories of who she was and who she was becoming.